الدين في حياة الإنسان المعاصر - أبو زايد, أحمد; العلان, منقذه (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
يناقش هذا البحث الأزمة الروحية الحاضرة لإنسان عصر العلم، ويحاول أن يقدم دراسة نقدية فلسفية تشرح ملامح هذه الأزمة ونتائجها وأسبابها الكامنة في التصور المادي للعالم الذي يقلص وجود الإنسان ويحرمه من كل أبعاده الروحية وما يتبع ذلك من اختناق روحي وفقدان للأمل وسيطرة للمادية والفردية المتنكرة للدين بحثاً عن مجتمع تحترم فيه الروح الإنسانية وتحفز لاستثمار قواها كاملة. This paper discusses the spiritual crisis of the present era of human science, and tries to offer a critical study of philosophical trends that explain the features of this crisis and its causes and consequences inherent in the materialist conception of the world. This reduces human rights and deprives Man of all spiritual dimensions. The consequent congestion and loss of spiritual hope and physical control of the individual lead to negate the search of a society for the human spirit that stimulates investment in full strength.